How to “Translate” Time - Movsisyan, Anaida (Bulletin of Yerevan University B: Philology, 2022)
The article makes an analysis of the issue of transferring of one of the phenomena presenting difficulty in translation, the so-called temporal space. In simultaneous translation, the author and translator are “contemporaries”. This fact facilitates the work of the translator. And if the translator and the author are not “contemporaries”, and the author has worked on the topics of his time and in the language of his time, the translator faces quite a difficult task, i.e. to translate it into the modern language making an attempt to convey to the reader the old style of the work. The use of obsolete words, historicisms, semantic and grammatical archaisms may contribute to the solution of this problem. When transferring the national-historical realities, one should choose the principle of translation, which will contribute to the transfer of temporal space. Neologisms and words of high style created by the translator can contribute to the solution of the considered problem. Of course, the talent of the translator, the good knowledge of the language of the original and the environment shown in the work are important along with this.